Discussion on the Impact of Campus Culture Construction on Ideological and Political Education and Learning Style Construction - Ye, Yujun (International Journal of Social Sciences and Public Administration, 2024)
In the contemporary education system, campus culture construction, ideological and political education and learning style construction complement each other. Campus culture is the embodiment of the university spirit. A good campus cultural environment plays an important role in the improvement and edification of students' moral quality. Therefore, campus culture construction plays an important role in the cultivation of students' ideological and political education. This paper will explore how campus culture construction affects ideological and political education and learning style. It has an impact.